1982
DOI: 10.1111/j.1365-3032.1982.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social situation on food consumption and growth in nymphs of the house cricket, Acheta domesticus

Abstract: Grouped nymphs of Acheta domesticus L. (Orth., Gryllidae), which mature faster than isolated ones (Chauvin, 1958), consumed more food per milligram of body weight and converted it to body tissue more efficiently than did isolated nymphs, during the fifth and sixth instars. Grouped nymphs, usually had fewer instars than isolated ones. Feeding and growth rates did not decline after isolation part-way through development. Previously isolated females, paired at 25 days, matured as rapidly as females paired through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the current study, we also observed that crowding could promote feeding on unfertilised eggs and accelerate nymphal development. These results are consistent with the study of Walter (1982) and provide further evidence of the physiological mechanisms underlying the group effect in nymphal crickets. Lee and Loher (1995) reported that nymphs of another burrowing cricket species, A. muticus, did not show aggressive behaviours towards each other until 10-15 days after hatching, suggesting that nymphs may live together for a certain time before dispersing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, we also observed that crowding could promote feeding on unfertilised eggs and accelerate nymphal development. These results are consistent with the study of Walter (1982) and provide further evidence of the physiological mechanisms underlying the group effect in nymphal crickets. Lee and Loher (1995) reported that nymphs of another burrowing cricket species, A. muticus, did not show aggressive behaviours towards each other until 10-15 days after hatching, suggesting that nymphs may live together for a certain time before dispersing.…”
Section: Discussionsupporting
confidence: 91%
“…However, some studies have reported that larval development rate, adult survivorship and adult body size all decrease as larval density increases because of intraspecific competition (Schneider et al, 2000;Gimnig et al, 2002;Wiwatanaratanabatr & Kittayapong, 2009). Walter (1982) found that group-reared nymphs of Acheta domesticus consumed approximately 40% more food than their isolated counterparts, suggesting that greater food consumption accounts for faster growth under grouped conditions. Walter (1982) found that group-reared nymphs of Acheta domesticus consumed approximately 40% more food than their isolated counterparts, suggesting that greater food consumption accounts for faster growth under grouped conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MCFARLANE (1962) also noted that grouped (10) crickets grew faster than crickets reared singly. When crickets show this group effect they eat more and grow more efficiently than the singly reared animals (WATLER 1982). Survival is also increased in grouped crickets over single crickets (MCFARLANE et al 1984) but attempts (MCFARLANE andALLI 1985, 1988) to determine the basis for the group effect have been unsuccessful.…”
Section: Rearing Densitymentioning
confidence: 99%
“…2 Craig W. Clifford and J. P. Woodring The group effect in the house cricket has been investigated by MCFARLANE 1962, MCFARLANE et al 1984, MCFARLANE and ALLI 1988, WATLER 1982. Protein and lipid requirements as well as requirements for vitamins E and K and minerals have been studied by MCFARLANE and associates (MCFARLANE 1964(MCFARLANE , 1972a(MCFARLANE , b, 1974(MCFARLANE , 1976a(MCFARLANE , b, 1978MEIKLE and MCFARLANE 1965).…”
Section: Introductionmentioning
confidence: 99%